Design and experimental study of a steam ejector refrigeration system - Fei WANG; Leihao WANG; Xiaokai PAN; Yanan YANG (Journal of Thermal Science and Technology, 2022)
More and more attention has been paid to ejector refrigeration system using low grade thermal for cooling. Ejector is the most important part of this system, and its operating condition and structure are the two important parameters affecting system performance, especially the NXP value of ejector is a hot research topic at present. The optimal NXP was found by many experimental or numerical studies, but the theory about how to design an optimum nozzle position was rare. In order to verify whether the NXP value calculated with the free beam theory is suitable for the ejector designed by thermodynamic method, an ejector and a steam ejector refrigeration facility were designed for experimental investigation with a thermodynamic model using real fluid properties. The experimental values were compared with the theoretical design values and the optimum nozzle exit position was studied in experiment, and then the effect of operating condition on system critical performance were researched with optimum NXP. The results indicate that the system acquired a COP of 0.17 at Tg=70℃, Te=15℃and Tc=28℃, the experimental value of ejector entrainment ratio matched satisfactorily with theoretical value well, and so did the critical back pressure. The system COP and cooling effect under designed NXP value were superior to those with ±10mm change.